Development of a MFL system with optical positioning for ferromagnetic plate inspection - A. Ahemadi; Abdelhalim Taieb brahimi (e-Journal of Nondestructive Testing)
This paper presents the development of a Magnetic Flux Leakage (MFL) based system for non-destructive testing